1996
DOI: 10.1097/00007890-199608150-00020
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cellular Viability in Warm Versus Cold Ischemia Conditions of Kidney Preservation

Abstract: We have determined the kinetics of the cellular viability ratio (CVR), defined as the number of living cells over the total cell count, in pig kidneys using propidium iodide and fluorescein diacetate staining, as a function of time and preservation conditions. The kidneys were preserved in warm or cold ischemia in order to mimic the conditions of transplantation from non-heart-beating donors or multiple removal with optimal preservation of the graft, respectively. To determine the CVR, the cells were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…Braun-Collins solution functions via hypothermic preservation in hyperosmotic solution, followed by a low cellular dehydration, thus avoiding consequent cell swelling. At greater temperatures, our results were similar to those obtained by Savioz et al (1996) with kidney preservation at 14°C. These authors demonstrated the lack of effectiveness of BraunCollins solution when its use was not associated with preservation at 4°C.…”
Section: Discussionsupporting
confidence: 89%
“…Braun-Collins solution functions via hypothermic preservation in hyperosmotic solution, followed by a low cellular dehydration, thus avoiding consequent cell swelling. At greater temperatures, our results were similar to those obtained by Savioz et al (1996) with kidney preservation at 14°C. These authors demonstrated the lack of effectiveness of BraunCollins solution when its use was not associated with preservation at 4°C.…”
Section: Discussionsupporting
confidence: 89%
“…Braun-Collins solution has been successfully used in preservation at 4°C of lung (Fukuse et al, 1996), liver (Adam et al, 1996), kidneys (Savioz et al, 1996) and heart (Demmy et al, 1997) tissues. At greater temperatures, our results were similar to those obtained by Savioz et al (1996) with kidney preservation at 14°C. These authors showed the low efficiency of Braun-Collins solutions when its use was not associated with the hypothermic principle.…”
Section: Discussionmentioning
confidence: 99%
“…Saline solution (0.9%) is commonly used as a conservation media for ovaries during short periods of time (Solano et al, 1994, Schernthaner et al, 1997and Azambuja et al, 1998, although this solution has not been tested as a medium for preantral follicle storage for longer periods. Braun-Collins solution is another medium that has been successfully used in the preservation of different organs, such as lungs (Fukuse et al, 1996), liver (Adam et al, 1996), kidney (Savioz et al, 1996) and heart (Demmy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For organ preservation and transplantation, it is extremely important to define the degree of ischemia reperfusion injury [3]. The circumstances of explantation, ischemic periods and the preservation solution are known to be highly important factors with regard to organ quality not only for the kidney [4, 5]. In general, 30–60 min ischemia time to explant kidneys from NHBD is considered to represent the maximum time limit for viable transplantation [4, 6].…”
Section: Introductionmentioning
confidence: 99%